1996
DOI: 10.1097/00043426-199602000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Effectiveness of Gastrostomy Feedings in Pediatric Cancer Patients

Abstract: GT feeding was associated with minor complications, but permitted effective nutritional support for pediatric cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 16 publications
6
57
0
1
Order By: Relevance
“…Our findings support those of Aquino et al [13] and Matthew et al [12], who showed that weight gain can occur with G-tubes in this patient population.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings support those of Aquino et al [13] and Matthew et al [12], who showed that weight gain can occur with G-tubes in this patient population.…”
Section: Discussionsupporting
confidence: 93%
“…We found that retrograde G-tube placement by radiology is possible in the majority of paediatric haematology/oncology patients without general anaesthesia, with a low percentage of major complications, and a decreased occurrence of minor complications, compared to published studies [12,13]. Our findings support those of Aquino et al [13] and Matthew et al [12], who showed that weight gain can occur with G-tubes in this patient population.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A secondary goal was to emphasize enteral feeding as the safest, most effective form of nutritional support. The algorithm also outlined specific durations of total parenteral nutrition (TPN), since short courses of this support are not beneficial (ASPEN, 1989) but do carry risk, notably of infection (Christensen et al, 1993;Mathew et al, 1996).…”
Section: Resultsmentioning
confidence: 99%